Isolation of Neutrophil Nuclei for Use in NETosis Assays - Dave Boucher (Bio-Protocol, 2019)
Neutrophils are critical immune cells that protect our body against invading pathogens. They generate antibacterial DNA structures called neutrophil extracellular traps (NET). Recently we identified a new mechanism that enables NET formation. We observed that following recognition of lipopolysaccharides, inflammatory caspases cleave Gasdermin D and enable NET generation (Chen et al., 2018). This protocol describes how we purify neutrophil nuclei to visualize NET formation by live microscopy. After neutrophil purification from murine bone marrow, neutrophils are lysed in a hypotonic buffer using a nitrogen cavitation device to prevent lysis of neutrophil granules and subsequent contamination by granules proteases. Lysed neutrophils are then centrifuged, and nuclei are counted. The protocol described here is straightforward and enables the study of early changes happening in the nuclei of neutrophils undergoing NETosis with limited contamination by granule proteases.